Gambaran Leukosit pada Proses Penyembuhan Patah Tulang Paha pada Tikus dengan Terapi Minyak Sasak Secara Topikal - Nurjunitar, Annita Vury; Gunanti, Gunanti; Noviana, Deni (Jurnal Veteriner; Vol 23 No 3 (2022), 2023)
Sasak oil is one of Indonesia traditional medicine products that can help the fracture healing. This study was aimed to analyze the leukocytes profile of femoral fracture healing process in rat using sasak oil therapy topically. This study used 28 male rats which were divided into four groups. All rats underwent closed fracture surgery of the mid-femoral diaphysis and intramedullary pin inserting. The group of P0 was control, P1 was given 0,1 mL of sasak oil twice a day, P2 was given 0,3 mL of sasak oil twice a day, and P3 was given 0,5 mL of sasak oil twice a day topically over the wound sutures for eight weeks. Blood sampling was conducted one day before surgery, the 2nd, 6th, and 8th week after surgery. Generally, leukocytes of the P3 group on the 2nd week after surgery decreased then increased on the 6th and 8th week, except neutrophils. On the 2nd week after surgery, neutrophils increased above normal significantly (P<0,05) compared to the value before surgery. On the 6th week leukocytes, lymphocytes, and monocytes increased insignificantly (P>0,05) compared to the 2nd week. Meanwhile, neutrophils decreased significantly (P<0,05). The increasing and decreasing of those blood cells were still within the normal range and not different significantly (P>0,05) with the 8th week. This study showed sasak oil at a dose of 0.5 mL (P3) given twice a day topically was more stable, and it could accelerate cell regeneration as well as it did not cause allergies.